What is `(24 x^3 y^2 + 12 x^3 y^4 - 18 x^4 y^3)/ (6xy^2)`
- print Print
- list Cite
Expert Answers
Tushar Chandra
| Certified Educator
calendarEducator since 2010
write12,554 answers
starTop subjects are Math, Science, and Business
The expression `(24x^3y^2+12x^3y^4-18x^4y^3)/(6xy^2)` has to be evaluated.
`(24x^3y^2+12x^3y^4-18x^4y^3)/(6xy^2)`
=> `(6xy^2(4x^2+2x^2y^2-3x^3y))/(6xy^2)`
=> `4x^2+2x^2y^2-3x^3y`
The required result is 4x^2+2x^2y^2-3x^3y
Related Questions
- Simplify: (24 x^3 y^2 + 12 x^3 y^4 - 18 x^4 y^3) ÷ (6xy^2)
- 1 Educator Answer
- if x+y +z =1 X^2+Y^2+Z^2=2 X^3+Y^3+Z^3=3 then find x^4 +y^4 +z^4=?use algebra
- 1 Educator Answer
- Solve for x and y : x^2-y^2=4; x+y=2
- 1 Educator Answer
- Which of the quadratic functions has the widest graph? A. y = (1/3)x^2 B. y = -4*x^2 C. y =...
- 2 Educator Answers
- Tell which statement is not true. 1. If x+2/x = 5+y/5, then 2/x = y/5 2. If x/3 = y/4, then x/y =...
- 1 Educator Answer
Wiggin42 | Student
I'm assuming you just want this simplified.
Start by canceling out the number 6 since its in all the coefficients. Divide each term by 6.
`(4x^3y^2 + 2x^3y^4 - 3x^4y^3)/(xy^2)`
Now we can cancel out the variable x since its in all the terms. When dividing exponents, just subtract.
`(4x^2y^2 + 2x^2y^4 - 3x^3y^3)/(y^2)`
``Now we can do the same thing with `y^2`
`4x^2 + 2x^2y^2 - 3x^3y`
``
Student Answers